Farm-Level Risk Factors Associated With Avian Influenza A (H5) and A (H9) Flock-Level Seroprevalence on Commercial Broiler and Layer Chicken Farms in Bangladesh - Gupta, Suman Das; Fournié, Guillaume; Hoque, Md. Ahasanul; Henning, Joerg (Frontiers in Veterinary Science, 2022)
A cross-sectional study was conducted to identify farm-level risk factors associated with avian influenza A H5 and H9 virus exposure on commercial chicken farms in Bangladesh. For broiler farms, both H5 and H9 seropositivity were associated with visits by workers from other commercial chicken farms (odds ratio [OR] for H5=15.1, 95% confidence interval [CI]: 2.8-80.8); OR for H9=50.1, 95% CI: 4.5- 552.7), H5 seropositivity was associated with access of backyard ducks (OR=21.5, 95% CI: 2.3-201.1) and H9 seropositivity with number of farm employees (OR=9.4, 95% CI: 1.1-80.6). On layer farms, both H5 and H9 seropositivity were associated with presence of stray dogs (OR for H5=3.1, 95% CI: 1.1-9.1; OR for H9=4.0, 95% CI: 1.1-15.3), H5 seropositivity with hatcheries supplying chicks (OR=0.0, 95% CI: 0.0-0.3), vehicles entering farms (OR=5.8, 95% CI: 1.5-22.4), number of farm employees (OR=5.8, 95% CI: 1.2-28.2) and burying of dead birds near farms (OR=4.6, 95% CI: 1.2-17.3); H9 seropositivity with traders supplying feed (OR=5.9, 95% CI: 1.0-33.9), visits conducted of other commercial poultry farms (OR=4.7, 95% CI: 1.1-20.6), number of spent layers sold (OR=24.0, 95% CI: 3.7-155.0) and frequency of replacing chicken droppings (OR=28.3, 95% CI: 2.8-284.2). Policies addressing these risk factors will increase the effectiveness of prevention and control strategies reducing the risk of avian influenza on commercial chicken farms.